Exploring of Potential of Cloud Computing for Small and Medium Enterprises - Shafinah Kamarudin; Ahmad Hidayat Ahmad Khalili; Zakry Fitri Abd. Aziz; Khairul Anuar Kamarudin; Amelia Natasya Abdul Wahab (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2022)
Business activities such as human resources management, payroll, finance, and accounting are crucial for Small and Medium Enterprises (SMEs). Therefore, adopting technologies such as cloud computing is expected to improve SMEs’ efficiency. The migration from current business practices to cloud computing amongst SME entrepreneurs remains a challenge. Therefore, this study presents a short review of cloud computing concepts, the characteristics, types of cloud computing service models, and also cloud computing deployment models. This study highlights the benefits and challenges faced by SMEs entrepreneurs in adopting cloud computing. Also, this study explores the existing cloud computing services provided for SMEs. The present study aims to provide a better understanding of cloud computing’s potential to be applied in helping SMEs manage their business activities.